Asesmen Aliran Kritis Sistem Pengelolaan Sampah Perkotaan di TPA Sampah - Annisa, Bismi (LPPM ITK, 2017)
Capacities of Cipayung landfill (final processing) has exceeded capacity. The composition of organic waste is the most dominant waste composition. This study aims to assess the critical flow of municipal solid waste management system in the Cipayung landfill thus be predicted or estimated improvement of waste management system in the landfill Cipayung. The research method using MFA STAN software for a period of one year beginning in 2017 until 2018. The results of this study are critical flow of waste management systems are in the process of sorting and empowerment are still done manually, so the impact on increasing the amount of garbage residue will be dumped in Cipayung landfill. Waste composition which includes the critical flow is organic waste, plastic, paper, glass and aluminum. All materials that are at a critical flow still can be empowered using mechanical sorting machines garbage. Management recommendation is to apply the technology of recycling, composting and RDF feedstock. The government should establish cooperation with the private sector to process waste into resources that extend the life of landfill serviceability. Through optimization scenario 1, the critical flow of waste management systems can be improved with a reduction of more than 50% of the waste to be dumped into landfill Cipayung.